Invariant Natural Killer T Cells Ameliorate Monosodium Urate Crystal-Induced Gouty Inflammation in Mice - Wang, Jie; Yang, Qibin; Zhang, Quanbo; Yin, Congcong; Zhou, Li; Zhou, Jingguo; Wang, Yangang; Mi, Qing-Sheng (Frontiers in Immunology, 2017)
Gout is an inflammatory arthritis caused by deposition of intra-articular monosodium urate (MSU) crystal. Previous studies have focused on resident macrophage, infiltrating monocyte, and neutrophil responses to MSU crystal; yet the mechanisms of cellular changes and the potential involvement of other regulatory immune cells remain largely unknown. Invariant natural killer T (iNKT) cells, an innate type of T cell, are involved in the development of a variety of inflammatory diseases. Here, we investigate the role of iNKT cells in MSU crystal-induced gouty inflammation. MSU crystal-induced inflammatory profiles in an air-pouch model were examined in iNKT-deficient CD1d knockout (KO) and wild-type (WT) control mice. To explore potential mechanisms of iNKT cell regulation of gouty inflammation, we co-cultured CD4+ or CD4- iNKT cells with bone marrow derived macrophages (BMDMs). We found that iNKT cells quickly migrated to the site of inflammation upon MSU crystal stimulation in WT mice. The total number of infiltrating cells in CD1d KO mice, especially neutrophils, was dramatically increased at 6h and 12h (P<0.01) post-MSU crystal challenge, compared to WT controls. BMDMs co-cultured with CD4+ iNKT cells produced less TNF- and expressed higher levels of M2 macrophage markers, including Clec7a, Pdcd1Ig2, and IL-4 (P<0.01), compared to BMDMs co-cultured with CD4- iNKT cells or conventional CD4+ T cells. CD4+ iNKT cells are one of the key regulators of MSU crystal-induced gouty inflammation through the control of macrophage polarization. iNKT cells may serve as a new therapeutic target for gout.